2020
DOI: 10.31557/apjcp.2020.21.5.1275
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Extract of Hizikia fusiforme Induces Apoptosis in B16F10 Mouse Melanoma Cells through ROS-Dependent Inhibition of the PI3K/Akt Signaling Pathway

Abstract: Background: Previous studies have reported that Hizikia fusiforme, an edible brown seaweed, has diverse health-promoting effects; however, evidence for its anti-cancer potential is still lacking. In this study, we examined the effect of ethanol extract of H. fusiforme (EHF) on the proliferation of B16F10 mouse melanoma cells. Methods: Analyses of cell viability and apoptosis were performed to study the actions of EHF on B16F10 cells. Cellular reactive oxygen species (ROS) and mitochondrial membrane potential (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Several studies have reported that ethanol extracts of H. fusiformis , fucoidan, and alginate isolated from H. fusiformis possess anti-apoptotic effects [ 7 , 10 , 106 ] ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have reported that ethanol extracts of H. fusiformis , fucoidan, and alginate isolated from H. fusiformis possess anti-apoptotic effects [ 7 , 10 , 106 ] ( Table 7 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have shown that the ethanol extract of H. fusiformis has potential anticancer activity. The mechanism is mediated by activation of the intrinsic and extrinsic apoptotic pathways; thus, ROS-dependent inactivation of PI3K/Akt signaling through apoptosis was induced in B16F10 mouse melanoma cells [ 106 ]. Similar results showed that the ethanol extract of H. fusiformis markedly suppressed the growth of PC3 cells by regulating the ROS-dependent pathway [ 107 ].…”
Section: Resultsmentioning
confidence: 99%
“…Coptidis Rhizoma was obtained from the Dong-Eui Korean Hospital of Dong-Eui University (Busan, Republic of Korea) and was refluxed with 1 L of 70% ethanol solution by sonication for 24 h, as previously described [ 34 ]. After filtering, the extract was concentrated with a rotary vacuum evaporator (Buchi Labortechnik, Flawil, Switzerland), followed by freezing-drying, and then stored at −80 °C.…”
Section: Methodsmentioning
confidence: 99%
“…On the other side, anticancer activity of marine phenols could be achieved by the suppression of the telomerase expression and activity or by the modulation of the proliferation signal pathways as reported and reviewed by others [40,59]. Numerous research studies have been conducted so far, investigating the anticancer activity of organic or water extracts obtained mostly from macro-and microalgae, sponges and tunicates [60][61][62][63][64][65][66][67][68]. As admonished by Rosa et al, it is necessary to characterize the chemical composition so that the activity can be associated with the presence of a certain metabolite.…”
Section: Anticancer Properties Of Marine-derived Phenolic Compoundsmentioning
confidence: 99%